The impact of Knowledge Management (KM) and Organizational Commitment (OC) on employee job satisfaction (EJS) in banking sector of Pakistan - Najeeb, Muhammad Mohsin; Hanif, Muhammad Imran; Abdul Hamid, Abu Bakar (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
Purpose: The purpose of this paper is to examine the impact of knowledge management practices and organizational commitment could be a way to nurture job satisfaction and examine how knowledge management practices and organizational commitment can increase individual employees’ job satisfaction. Design/methodology/approach: A theoretical model concerning the connections between sixfacets of Knowledge Management (knowledge acquisition, knowledge sharing, knowledge creation, knowledge application,knowledge codification and knowledge retention), two facets of Organizational Commitment (Keeping up organizational image and Responding to organizational greediness)and job satisfaction is proposed. Then data is collected through face to face questionnaire and also online web based questionnaires and sample is selected on convenience based from the banking sector organization of Pakistan. Findings:organization commitmentand knowledge management process in one’s working environment is significantly linked with high employee job satisfaction. Especially intra-organizational knowledge sharing knowledge application and knowledge creationalso organization commitment (coping with attachment) seems to be a key factors promoting satisfaction with one’s job in most employee. Practical implications:organization commitment and knowledge management has a strong impact on employee job satisfaction, and therefore, managers are advised to implement knowledge management and organization commitment activities in their organizations, not only for the sake of improving knowledge worker performance but also for improving their well-being at work. Originality/value: This paper produces knowledge on a practices of KM and organizational commitment that has been largely unexplored in previous all research, individual job satisfaction. Also, it promotes the knowledge management and organizational commitmentliterature to the next stage where the impact of knowledge management and organizational commitment is not explored as a “one size fits all” type of a phenomenon, but rather as a contingent and contextual issue. Keywords:Knowledge Management, Knowledge Management Practices,Knowledge Acquisition, Knowledge Sharing, Knowledge Creation, Knowledge Codification, Knowledge Retention, Organizational Commitment, Job satisfaction.